1982
DOI: 10.1093/genetics/102.1.39
|View full text |Cite
|
Sign up to set email alerts
|

A STUDY OF rDNA MAGNIFICATION PHENOMENON IN A REPAIR-RECOMBINATION DEFICIENT MUTANT OF DROSOPHILA MELANOGASTER

Abstract: The rDNA magnification process consists of a rapid and inheritable rDNA increase occurring in bobbed males: in a few generations the bb loci acquire the wild-type rDNA value and reach a bb+ phenotype.—We have analyzed the rDNA magnification process in the repair-recombination-deficient mutant mei9a, both at the phenotypical and rDNA content levels. In mei9a bb double mutants the recovery of bb+ phenotype is strongly disturbed and the rDNA redundancy value fails to reach the wild-type level. The strong effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
1
1

Year Published

1987
1987
1989
1989

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
2
1
1
Order By: Relevance
“…In summary, our results confirm the observation by Polito et al (1982) that mei-9 a inhibits magnification and demonstrate that mei-9" has a similar, although less severe inhibitory effect. They show that two reduction-of-function alleles at a given locus may not have the same effect on a given process, in this case, magnification.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In summary, our results confirm the observation by Polito et al (1982) that mei-9 a inhibits magnification and demonstrate that mei-9" has a similar, although less severe inhibitory effect. They show that two reduction-of-function alleles at a given locus may not have the same effect on a given process, in this case, magnification.…”
Section: Discussionsupporting
confidence: 92%
“…Hawley & Tartof (1983) and Hawley et al (1985) further observed that mei-9", a repair replication-defective mutation (Nguyen & Boyd, 1977), had little or no effect on magnification. This observation was in apparent conflict with a previous report that mei-9 a inhibits magnification (Polito et al 1982).…”
Section: Introductioncontrasting
confidence: 94%
See 2 more Smart Citations